Systemic Absorption and Side Effects of Locally Injected Glucocorticoids. Issue 4 (29th March 2019) - Stout, Alison; Friedly, Janna; Standaert, Christopher J.
Abstract : Local glucocorticoid injections are often used to treat joint, soft tissue, or spinal pain, but the systemic side effects associated with these injections are poorly understood and not well recognized. There are significant known risks to systemic administration of glucocorticoids. However, there are no guidelines that address issues of systemic absorption, overall systemic risks, or other side effects of locally injected glucocorticoids. For this review, a literature search was performed, and the available evidence on systemic absorption and clinical side effects of intra‐articular and epidural glucocorticoids was synthesized. The goal was to improve clinical understanding of risks associated with these injections. Existing data suggest there is significant individual variability in the amount of systemic absorption and clinical effects of locally injected glucocorticoids. However, it is clear that both intra‐articular and epidural injections can have systemic effects for weeks and that complications may be associated with their use, including Cushing syndrome, loss of bone density, infection, and hyperglycemia. The concurrent use of oral steroids, the number of injections, and the type and dose of glucocorticoids used all are important considerations in estimating risks. The total dose calculation of cumulative glucocorticoid exposure should include all local injections. Caution should be exercised when local glucocorticoid injections are used in higher risk patients, such as postmenopausal women, people with diabetes, and those considering surgery in the near term. Better provider awareness of possible systemic risks should improve decision making and informed consent with patients when considering intra‐articular and epidural steroid injections for painful conditions. Level of Evidence: IV